2010
DOI: 10.1002/bse.703
|View full text |Cite
|
Sign up to set email alerts
|

Green consumer behaviour: an experimental analysis of willingness to pay for remanufactured products

Abstract: Products' end-of-life management has recently become a critical business issue. One of the possible end-of-life strategies is remanufacturing, which can provide competitive advantages through material and energy savings. Beyond industrial organization challenges, there is a question about the interest of developing a green marketing strategy for remanufactured products. Indeed, remanufactured products can be considered as green products since their industrial process has environmental benefits. Our paper asks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
217
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(250 citation statements)
references
References 34 publications
(33 reference statements)
15
217
0
1
Order By: Relevance
“…Price premium for green products is limited [33] and willingness to buy is strongly related to the ability of informing customers about the benefit of purchasing green [34,35]. The consumption of environment-friendly alternatives seems also affected by frequency of use [36] and level of functional risk [37].…”
Section: Metalevel Contributions and Challengesmentioning
confidence: 99%
“…Price premium for green products is limited [33] and willingness to buy is strongly related to the ability of informing customers about the benefit of purchasing green [34,35]. The consumption of environment-friendly alternatives seems also affected by frequency of use [36] and level of functional risk [37].…”
Section: Metalevel Contributions and Challengesmentioning
confidence: 99%
“…The fact remains the same that until and unless customers are not receiving proper information about the green product, it is quite normal that they will consider green product as an inferior one when compared to the conventional product (Michaud and Llerena, 2011). At the same time, customers will not buy a product just because it is green; they are not ready to compromise with its quality (Braimah and Tweneboah-Koduah, 2011).…”
Section: Research Implication and Discussionmentioning
confidence: 99%
“…Michaud and Llerena (2011) investigate consumers' willingness to pay (WTP) for remanufactured products by using experimental auctions. They concluded that a large number of consumers assume remanufactured products to have a lower quality level than that of new products.…”
Section: Literature Reviewmentioning
confidence: 99%